ANALISIS PELAKSANAAN PASAL 2 HURUF B PERATURAN MENTERI ENERGI DAN SUMBER DAYA MINERAL NOMOR 28 TAHUN 2016 TENTANG TARIF TENAGA LISTRIK YANG DISEDIAKAN OLEH PT PERUSAHAAN LISTRIK NEGARA (JURNAL HUKUM DAS SOLLEN, 2021)
AbstractThe regulation of the DPD is regulated in Article 22D of the 1945 Constitution, however, since the formation of the DPD RI, the position of the DPD in the Indonesian state administration system is still weak. Further arrangements are regulated in Law no. 27 of 2009 concerning the MPR, DPR, DPD, and DPRD (MD3) and Law no. 12 of 2011 concerning the Establishment of Legislation (P3). In these two laws, the DPD's authority in the field of legislation was reduced so that it was not in accordance with the 1945 Constitution. Therefore, the DPD submitted a judicial review of the two laws to the Constitutional Court. From the material test, the Constitutional Court Decision No. 92/PUU-X/2012, which places the DPD as an institution that has more meaning than before.